صياغة المفاهيم الهندسية في الكتاب المدرسي لمادة الرياضيات لصفوف المرحلة الأساسية (9-1) بالجمهورية اليمنية وعلاقتها بالتحصيل الهندسي لدى التلاميذ - صالح محسن محسن بهوث, عبده (جامعة محمد الخامس، كلية علوم التربية-الرباط, 2018)
The purpose of this study is to find out to what extent the geometric concepts in the mathematical textbooks of basic grades (1-9) adhere to Van Hiele model and their relation to students' geometric thinking level. The research materials included all of the geometric expressions of geometric concepts (square, rectangle, rhombus, parallelogram) in the mathematical textbooks for grades (1-9) which were approved by the Ministry of Education in the academic year 2014-2015. The sample of the study consisted of 300 male and female students were selected from (8) educational institutions in Dhamar city using multistage cluster random sampling method. These students completed their basic school and about to join secondary school. The framework for the data analysis was designed based on The Van Hiele geometric thinking model including the four levels of Van Hiele, All the geometric expressions in mathematical textbooks were classified based on Van Hiele's geometric thinking model of basic grades (1-9). Achievement test was also developed including the four levels of Van Hiele's thinking model, It was carried out to measure students' geometric thinking level of geometric concepts. The findings of the study revealed that the formulation of the geometric concepts in the mathematical textbooks for basic grade (1-9) corresponds in a weak degree to Van Hiele model based instruction, moving quickly from level 1 to level 2 and from level 3 to level 4. It is also found that the geometric expressions are presented in unsystematic way where these expressions are presented in (N) level and then again in(N-1) level. In addition, most of the geometric expressions were identified in the Van Hiele's second geometric thinking level with students' weakness in geometric thinking. ( 25.7%) of students were found lower than the first level (visualization), (68.7%) of students at the first level (visualization), (2%) at the second level (analysis), (0.3%) of students in the fourth level (formal deduction), and(3.3%) were outside the rankings. Finally, the results revealed that there was a strong correlation (0.95) between the corresponding degree of the geometric concepts formulation in the mathematical textbooks for the basic grade (1-9) and Van Hiele's geometric thinking levels among students who completed their basic grade studies and are about to join their secondary school.
(الأسس التعليمية‏ النموذج فان هيل نموذجا)
Keywords: الكتاب المدرسي; الرياضيات; المرحلة الأساسية; نموذج; تلميذ; التحصيل الهندسي; الجمهورية اليمنية; مفهوم; مادة